Tính: 3 x 4 x 7/7 x 3 x 6 =... 5 x 8 x 13/ 12 x13 x 5 =...
Tính
18/45 - 4/12 - 6/9 - 21/35
4/3 + 3/5 + 7/3 + 2/5 + 1/3
7/25 x 39/14 x 50/78
1/3 x 4/5 x 1/3 x 6/5
6/7 x 8/13 + 6/7 x 9/13 - 3/13 x 6/7
a) \(\frac{18}{45}-\frac{4}{12}-\frac{6}{9}-\frac{21}{35}=\frac{2}{5}-\frac{1}{3}-\frac{2}{3}-\frac{3}{5}\)
\(=\left(\frac{2}{5}-\frac{3}{5}\right)-\left(\frac{1}{3}+\frac{2}{3}\right)\)
\(=\frac{-1}{3}-1\)
\(=\frac{-4}{3}\)
b) \(\frac{4}{3}+\frac{3}{5}+\frac{7}{3}+\frac{2}{5}+\frac{1}{3}=\left(\frac{4}{3}+\frac{7}{3}+\frac{1}{3}\right)+\left(\frac{3}{5}+\frac{2}{5}\right)\)
\(=4+1=5\)
c) \(\frac{1}{3}.\frac{4}{5}.\frac{1}{3}.\frac{6}{5}=\frac{8}{75}\)
d) \(\frac{6}{7}.\frac{8}{13}+\frac{6}{7}.\frac{9}{13}-\frac{3}{13}.\frac{6}{7}\)
\(=\frac{6}{7}.\left(\frac{8}{13}+\frac{9}{13}-\frac{3}{13}\right)\)
\(=\frac{6}{7}.\frac{14}{13}\)
\(=\frac{12}{13}\)
Bài 1 Tìm x,biết
x.3/5=2/3
x.7/17=17/8
3/4 chia x=-7/12
3/8 - 1/6.x=1/4
1/3+1/2 chia x=-4
Bài 2 Tính
-6/11 chia [3/5 . 4/11]
7/12 + 5/12 chia 6 -11/36
[4/5 + 1/2] chia [3/13 - 8/13]
[2/3 - 1/4 + 5/11] chia [5/12 + 1 -7/11]
*Dấu . là dấu nhân nha mn*
Bài 1:
a: \(x=\dfrac{2}{3}:\dfrac{3}{5}=\dfrac{2}{3}\cdot\dfrac{5}{3}=\dfrac{10}{9}\)
b: \(x=\dfrac{17}{8}:\dfrac{7}{17}=\dfrac{17}{8}\cdot\dfrac{17}{7}=\dfrac{289}{56}\)
c: \(x=-\dfrac{3}{4}:\dfrac{7}{12}=\dfrac{-3}{4}\cdot\dfrac{12}{7}=\dfrac{-63}{28}=-\dfrac{9}{4}\)
d: \(\Leftrightarrow x\cdot\dfrac{1}{6}=\dfrac{3}{8}-\dfrac{1}{4}=\dfrac{1}{4}\)
hay \(x=\dfrac{1}{4}:\dfrac{1}{6}=\dfrac{3}{2}\)
e: \(\Leftrightarrow\dfrac{1}{2}:x=-4-\dfrac{1}{3}=-\dfrac{17}{3}\)
hay \(x=-\dfrac{1}{2}:\dfrac{17}{3}=\dfrac{-3}{34}\)
Tính bằng cách thuận tiện nhất:
a) 16, 2 x 3, 7 + 5, 7 x 16, 2 - 7, 8 x 4, 8 - 4, 6 x 7, 8 : 11, 2 + 12, 3 + 13, 4 - 12, 6 - 11, 5 - 10, 4
Tính:
a) 2^5 x 13^12 x 7^8 : 27 x 13^10 x 7^9
b) 2^n x 11 x 3 : 6^n x 3
c) 5^5 x 7 x 9^5 : 15^10
d) 7 x 8^10 x 27^9 - 8 x 9^13 x 2^27 : 7 x 6^26 x 2^2 - 2^4 x 8^3 x 27^9
e) 2^2^1^2015
f) 2015^0^2015^0^2015
5/6 + 5/8 + 3/4
12/15 + 3 + 3/5
4/3 x 7/8 x 5
8/9 x 6/5 : 3
7/12 + 5/8 x 4/3 - 3/4
(8/5 - 7/6) : 13/15 + 1/4
tính bằng cách thuận tiện nhất a, \(\dfrac{5}{13}\)x\(\dfrac{4}{15}\)x13= b, (\(\dfrac{3}{7}\)+\(\dfrac{5}{2}\))x\(\dfrac{7}{5}\)= c, \(\dfrac{1}{5}\)x\(\dfrac{11}{18}\)+\(\dfrac{11}{18}\)x\(\dfrac{3}{5}\)=
\(a,\dfrac{5}{13}\times\dfrac{4}{15}\times13=\dfrac{5\times4\times13}{13\times5\times3}=\dfrac{4}{3}\\ b,\left(\dfrac{3}{7}+\dfrac{5}{2}\right)\times\dfrac{7}{5}=\dfrac{3}{7}\times\dfrac{7}{5}+\dfrac{5}{2}\times\dfrac{7}{5}=\dfrac{3}{5}+\dfrac{7}{2}=\dfrac{6}{10}+\dfrac{35}{10}=\dfrac{41}{10}\\ c,\dfrac{1}{5}\times\dfrac{11}{18}+\dfrac{11}{18}\times\dfrac{3}{5}=\dfrac{11}{18}\times\left(\dfrac{1}{5}+\dfrac{3}{5}\right)=\dfrac{11}{18}\times\dfrac{4}{5}=\dfrac{22}{45}\)
a) -12+(x-9)<0 tìm x thuộc Z
b)x-(13-x)=-24+(-7+x)
c) (x - 7)+( 5-x)=12-(-8+x)
d)5(x-6)-2(x+3)=12
e)3(x-4)-(8-x)=12
f) 7(x-3)-5(3-x)=11x-5
g) 7(x-9)-5(6-x)=-6+11x
a) -12+(x-9)<0 tìm x thuộc Z
b)x-(13-x)=-24+(-7+x)
c) (x - 7)+( 5-x)=12-(-8+x)
d)5(x-6)-2(x+3)=12
e)3(x-4)-(8-x)=12
f) 7(x-3)-5(3-x)=11x-5
g) 7(x-9)-5(6-x)=-6+11x
Tính:
a) 2^5 x 13^12 x 7^8 : 2^7 x 13^10 x 7^9
b) 2^n x 11 x 3 : 6^n x 3
c) 5^5 x 7 x 9^5 : 15^10
d) 7 x 8^10 x 27^9 - 8 x 9^13 x 2^27 : 7 x 6^26 x 2^2 - 2^4 x 8^3 x 27^9
e) 2^2^1^2015
f) 2015^0^2015^0^2015